Promising cell systems for targeted delivery of nano- and microcarriers loaded with drugs or biomolecules (review) - L. A. Miroshnichenko; T. Yu. Polyakova; I. A. Khlusov; E. Yu. Avdeeva; V. G. Luzhanin; E. I. Molokhova; A. L. Golovanenko; M. Yu. Khlusova; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. Cellular systems for targeted delivery of drug and biological molecules (drug delivery systems, DDSs) are currently considered as a promising solution to the problems of nano- and micro-sized drug carriers.Text. The review briefly examines fundamental and applied issues in the development of cellular DDSs, the morphofunctional diversity of which theoretically makes it possible to solve the problems of pharmacotherapy of various diseases. Sources are presented summarizing clinical protocols for the use of cellular DDSs, which are, however, limited to antitumor and anti-inflammatory therapy. The advantages, as well as particular and general disadvantages of using certain cells (blood cells, immunocytes, stem cells) as promising platforms for translation into clinical practice of delivery vehicles for various drugs (antibiotics, cytostatics, monoclonal antibodies, enzymes, etc.) loaded into nano- and micro-sized DDSs.Conclusion. Despite the obvious and impressive successes of fundamental and applied research in this area, a difficult path lies ahead in optimizing the processes of targeted delivery and controlled release of drug and biological molecules using cellular DDSs.